Hypoxia and angiogenic biomarkers in prostate cancer after external beam radiotherapy (EBRT) alone or combined with high-dose-rate brachytherapy boost (HDR-BTb). (August 2019) - Bhattacharya, Indrani S.; Taghavi Azar Sharabiani, Mansour; Alonzi, Roberto; Hoskin, Peter J.
Highlights: Angiogenic and hypoxia biomarkers investigated as predictors of outcome after radiotherapy for localised prostate cancer. Increased expression of osteopontin (OPN) and glucose transporter 1 (GLUT1) predicted worse biochemical relapse free survival (BRFS). Increased GLUT1 predicted worse distant metastasis free survival. Increased microvascular density and osteopontin expression, and reduced GLUT1 predicted improved BRFS in patients receiving EBRT + HDR-BTb. Angiogenic and hypoxia biomarkers may predict outcome and benefit of dose escalation. Abstract: Purpose: To investigate angiogenic and hypoxia biomarkers to predict outcome in patients receiving external beam radiotherapy (EBRT) alone or combined with high-dose-rate brachytherapy boost (HDR-BTb) for localised prostate cancer. Methods: Prostate biopsy samples were collected prospectively in patients entered into a phase 3 randomised controlled trial of patients receiving EBRT or EBRT + HDR-BTb. Univariate and multivariate analyses using Cox proportional hazards model were performed to identify associations between immunohistochemical staining of hypoxia inducible factor 1 alpha (HIF1α), glucose transporter 1 (GLUT1), osteopontin (OPN) and microvessel density (MVD) using CD-34 antibody with clinical outcome. The primary endpoint was biochemical relapse free survival (BRFS) and secondary endpoint was distant metastasis free survival (DMFS). Results: Immunohistochemistry was available for 204 patients. Increased OPN (Hazard ratio [HR] 2.38, 95% Confidence Interval [CI] 1.06–5.34, p  < 0.036) and GLUT1 (HR 2.36, 95%CI 1.39–4.01, p  < 0.001) expression were predictive of worse BRFS. Increased GLUT1 expression (HR 2.22, 1.02–4.84, p  = 0.045) was predictive of worse DMFS. Increased MVD (CD-34) (HR 1.82, 95%CI 1.06–3.14, p  = 0.03) and OPN (HR 1.82, 95%CI 1.06–3.14, p  = 0.03) but reduced GLUT1 expression (HR 0.40, 95%CI 0.20–0.79, p  = 0.009) were predictive of improved BRFS in patients receiving EBRT + HDR-BTb. Conclusion: Our data suggest angiogenic and hypoxia biomarkers may predict outcome and benefit of dose escalation, however further validation in prospective studies including hypoxia modification is needed. Trial registration number ISRCTN98241100, registered with ISRCTN at http://www.controlled-trials.com/isrctn/.